Coram boy - Gavin, Jamila (London : Egmont, 2004)
In the mid-eighteenth century, an unsavory character and his simpleton son become involved in the lives of a wealthy English family when that family's eldest son is disinherited because of his love of music.
Young Adult.
Young Adult
Keywords: Foundlings -- Fiction; Historical fiction; Historical fiction; Orphans -- Fiction; Great Britain -- Social life and customs -- 18th century -- Fiction; Great Britain -- Social life and customs -- Fiction